Wedge splitting test method: quantification of influence of glued marble plates by two-parameter fracture mechanics - S. Seitl; B. Nieto García; I. Merta (Fracture and Structural Integrity)
In the present paper, the well-known wedge splitting test (WST) is applied on specimens with different geometries (S= 150, 200, 300 mm) and variants of the specimens’ configurations. K-calibration (B1) and T-stress (B2) calibration curves for such specimens are introduced. The objective was to compare and discuss the values of the calibration curves dependent on the specimen’s geometries and on three different specimens' configurations: homogenous specimen; specimen with marble plates forming the groove for load application and specimen with glued marble plates.